ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN E-WALLET PADA GENERASI Z - Ayu Kusumaning Tyas Eka Putri; Wulandari, Ika (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to answer the question, "How does Gen Z feel about e-wallets in general?" by looking at how variables such as transaction security, usability, and perceived usefulness affect e-wallets. One hundred people who were at least 17 years old and regularly used electronic wallets participated in the study, which used a quantitative approach with associative techniques. Survey Data were analyzed using multiple linear regression. We perform testing of classical assumptions, including multicollinearity, heterogeneity, and normality, to ensure model validity. Factors including transaction security, ease of Use, and perceived usability have had a beneficial and substantial impact on e-wallet usage among Generation Z members. This study aims to answer the question, "How does Gen Z feel about e-wallets in general?" by looking at how variables such as transaction security, usability, and perceived usefulness affect e-wallets. One hundred people who were at least 17 years old and regularly used electronic wallets participated in the study, which used a quantitative approach with associative techniques. Survey Data were analyzed using multiple linear regression. We perform testing of classical assumptions, including multicollinearity, heterogeneity, and normality, to ensure model validity. Factors including transaction security, ease of Use, and perceived usability have had a beneficial and substantial impact on e-wallet usage among Generation Z members.